Laparoscopic cholecystectomy completely guided by indocyanine green fluorescence in a patient with gallstone: A case report. (November 2021) - Takahashi, Junji; Yoshida, Masashi; Nakaseko, Yuichi; Nakashima, Keigo; Kamada, Teppei; Suzuki, Norihiko; Ohdaira, Hironori; Suzuki, Yutaka
Abstract: Introduction: We report the execution of a cholecystectomy under complete fluorescence guidance using near-infrared camera images without switching to the white light mode, a method that has not been reported previously. Presentation of case: An Asian woman in her fifties with no history of abdominal surgery was administered indocyanine green (ICG, 25 mg) intravenously 16 h before the surgery. Laparoscopic surgery was performed using VISION SENSE® with the four-trocar technique. The entire laparoscopic procedure was performed under fluorescence guidance. The orientation of the gallbladder neck can be recognized from the beginning of the procedure, and the serosal first incision could be positioned appropriately. All procedures were performed while the common bile duct was visualized. Peeling around the cystic duct and gallbladder bed was appropriately guided by ICG fluorescence. Discussion: This method may be a safer form of surgery because the fluorescence did not disturb the surgical procedures. Conclusion: Since this method was successful in this case, a case series is warranted. Highlights: A cholecystectomy under complete fluorescence guidance (C-CFG) was performed. C-CFG was performed without switching to the white light mode. All procedures can be performed while visualizing the common bile duct. Peeling around the cystic duct was appropriately guided by ICG fluorescence. The line to be peeled is clearly recognized while being exfoliated from the liver.